JectOS® versus PMMA vancomycin-loaded cement: The biomechanical and antimicrobial properties - Singh, Vivek Ajit; Chang, Chee Wei; Haseeb, Amber; Shanmugam, Rukmanikanthan; Teh, Cindy Shuan Ju (SAGE Publications (UK and US), 2019)
Purpose: Bone cement is commonly used as a void filler for bone defects. Antibiotics can be added to bone cement to increase local drug delivery in eradicating infection. After antibiotic elution, nonbiodegradable material becomes an undesirable agent. The purpose of this study was to evaluate effects of addition of vancomycin on the compressive strength of injectable synthetic bone substitute, JectOS ® . JectOS, a partially biodegradable cement that over time dissolves and is replaced by bone, could be potentially used as a biodegradable antibiotic carrier. Methods: Vancomycin at various concentrations was added to JectOS and polymethyl methacrylate (PMMA). Then, the cement was molded into standardized dimensions for in vitro testing. Cylindrical vancomycin–JectOS samples were subjected to compressive strength. The results obtained were compared to PMMA-vancomycin compressive strength data attained from historical controls. The zone of inhibition was carried out using vancomycin-JectOS and vancomycin-PMMA disk on methicillin-resistant strain culture agar. Results: With the addition of 2.5%, 5%, and 10% vancomycin, the average compressive strengths reduced to 8.01 ± 0.95 MPa (24.6%), 7.52 ± 0.71 MPa (29.2%), and 7.23 ± 1.34 MPa (31.9%). Addition of vancomycin significantly weakened biomechanical properties of JectOS, but there was no significant difference in the compressive strength at increasing concentrations. The average diameters of zone of inhibition for JectOS-vancomycin were 24.7 ± 1.44 (2.5%) mm, 25.9 ± 0.85 mm (5%), and 26.8 ± 1.81 mm (10%), which outperformed PMMA. Conclusion: JectOS has poor mechanical performance but superior elution property. JectOS-vancomycin cement is suitable as a void filler delivering high local concentration of vancomycin. We recommended using it for contained bone defects that do not require mechanical strength. © The Author(s) 2019.